Skupno branje Ostržka z vidika Kohlbergovih stopenj moralnega razvoja - Legvart, Polona (Revija za elementarno izobraževanje, 2013)
Group Reading Pinocchio from the Perspective of Kohlberg’s Stages of Moral Development. In the project of group-reading Collodi’s Pinocchio at the second grade of primary school we included Kohlberg’s model of moral development stages. We encouraged pupils to respond to a large number of moral dilemmas occurring throughout the text. We have discovered that children’s moral judgments slightly exceeded both stages of the pre-conventional level. In some cases, they even reached the fourth conventional stage. Similar results have been observed in some other studies of child’s moral development based on Kohlberg’s model. However, our main objective was to find those didactical approaches to reading literary texts, which could help one infer the moral issues within the text, thus supporting implicit moral education of pupils. Kohlberg’s model was of great help in achieving our objective systematically and on the basis of universal ethics, with righteousness as the highest value, rather than in an anecdotic or moralistic way. We were particularly interested in the so-called permissiveness, a concept that had existed under different formulations already in Collodi’s times and had expressed itself through typical misconceptions, such as indulgence means freedom, having no plan enables spontaneity, disobedience is an expression of individuality, messiness stands for art, and confusion is supposed to be a pedagogical concept. Our findings speak in favour of the process-development didactic model of moral education that could be described as a post-permissive approach.